Digging deep and running dry—the adoption of borewell technology in the face of climate change and urbanization - Linda Steinhübel; Johannes Wegmann; Oliver Mußhoff (Agricultural Economics, 2020)
In this article, we analyze the effects of household location and weather variability on the adoption of borewell technology along the rural–urban interface of Bangalore, India. Understanding these effects can help to design policies that ensure smallholders' livelihoods and the functioning of ecosystems in drought-prone areas. First, a theoretical framework was developed that conceptualizes how household location and weather can influence farmers' adoption decisions. Then, an empirical analysis based on a primary data set collected in 2016 and 2017, covering 576 farm households, was conducted. With a semiparametric hazard rate model, determinants of the borewell adoption rate were analyzed. Different rainfall variables were included to capture the effect of changing climate conditions as well as a two-dimensional penalized spline (P-spline) to estimate the effects of household location. Results show that proximity to Bangalore, but also secondary towns accelerate adoption rates. In terms of weather variability, the study finds that a higher amount of total annual rainfall decelerates adoption rates, whereas higher amounts of rainfall during the southwest monsoon (the most important cropping season) accelerate adoption.
Keywords: 330; borewell technology; climate change; India; semiparametric duration models; urbanization